Anti-infrared stealth fabric and preparation method thereof
By using specific combinations of materials and processes in infrared stealth fabrics, an anti-infrared stealth fabric with excellent infrared stealth performance was prepared, solving the problem of poor stealth effect of existing fabrics in the infrared band.
Patent Information
- Application Number
- CN202510063861.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The existing infrared stealth fabrics have insufficient infrared transmittance and absorption in the 8-14μm band, resulting in poor stealth effect.
An infrared stealth coating consisting of microcapsule phase change material, low infrared emissivity powder, low infrared emissivity visible pigment, modified silane adhesive and modified graphene is prepared, combined with silicon oxide gel thermal insulation layer, an infrared anti-infrared stealth fabric is prepared.
The infrared emissivity of the fabric is significantly reduced, and its stealth effect in the 8-14μm band is improved, which greatly reduces the detectability of the fabric in the infrared detection system.
Smart Images

Figure BDA0005243665910000171 
Figure BDA0005243665910000172 
Figure BDA0005243665910000181
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stealth fabrics, and in particular to an anti-infrared stealth fabric and a preparation method thereof. Background Art
[0002] With the development of society and the continuous progress of science and technology, the detection technology in modern military science and technology of various countries has become increasingly mature and has become one of the necessary means of military reconnaissance. The threats faced by military facilities and weapons and equipment are increasing. Stealth technology uses various technical means to change the detectable characteristic information of the target, reduce the probability of being discovered and identified by the detection system, and thus improve the survivability of military targets. Modern stealth technology mainly includes visible light stealth, radar stealth, infrared stealth and magnetic stealth, among which infrared stealth technology plays an important role. Infrared stealth technology mainly reduces the detectability of the target by reducing or changing the infrared radiation characteristics of the target, such as changing the infrared radiation characteristics of the target, reducing the infrared radiation intensity of the target, and adjusting the propagation path of infrared radiation. Low-emissivity materials are a type of low-infrared radiation materials that can reduce the infrared emissivity and infrared radiation characteristics of the surface of military targets, making them difficult to be detected and identified by infrared detection systems. Low-infrared emissivity materials can be divided into inorganic low-emissivity materials, organic low-emissivity materials and organic-inorganic composite low-emissivity materials according to their chemical composition. Graphite has excellent properties, good chemical stability against acid, alkali and organic solvent corrosion; graphite also has good toughness and can be made into continuous thin sheets. Under normal temperature conditions, when the temperature changes drastically, the volume of graphite does not change much, no cracks will occur, and the performance of graphite is basically unaffected. Therefore, as a coating filler, it can form a good shielding layer.
[0003] Literature reports that the properties of adhesives have a great influence on the absorption of coatings in the infrared band. As an important component of infrared stealth coatings and functional coatings, adhesives need to have good physical and mechanical properties, high infrared transparency, low infrared emissivity, good compatibility with fillers, and the ability to wrap and adhere the fillers to the base fabric. During use, their own performance is stable and the infrared characteristics of the fillers can be protected. The atmospheric window 8-14μm band is an important working band for infrared detectors. The infrared transmittance and absorptivity of adhesives in the 8-14μm band directly determine the stealth effect of the adhesive. Research on high-performance infrared adhesives has also been paid attention to.
[0004] A Chinese invention patent with publication number CN105316945A discloses a double-sided coated fabric, a double-sided coated fabric, the coating of which is composed of 55-70% by mass of polyurethane PU resin, 5-20% cobalt inorganic pigment, 10-25% hollow glass microspheres of about 70μm (200 mesh), and 0-15% microcapsule phase change material. The double-sided coated fabric prepared by the invention has poor stealth. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide an anti-infrared stealth fabric and a preparation method thereof.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions:
[0007] An anti-infrared stealth fabric comprises, from the outside to the inside, an infrared camouflage surface layer and a heat insulation layer, wherein the infrared camouflage surface layer comprises, from the outside to the inside, an infrared stealth coating layer and a fabric layer;
[0008] The infrared stealth coating comprises the following raw materials in parts by weight: 9-15 parts of microcapsule phase change material, 8-10 parts of low infrared emissivity powder, 2-3 parts of low infrared emissivity visible light pigment, 6-10 parts of adhesive, 3-5 parts of cross-linking agent, 4-6 parts of thickener, and 100 parts of deionized water;
[0009] The adhesive is prepared by the following method:
[0010] S1: Under nitrogen protection, dichloromethane and aminoethylaminoisobutylmethylsiloxane terminated with dimethylsiloxane were added to the reactor, stirred, and siloxane acetyl chloride and triethylamine were slowly added dropwise at 0°C, reacted for 15-30 minutes, and then siloxane acetyl chloride and triethylamine were slowly added dropwise. The reaction was continued for 0.5-1 hour, and the modified silane was obtained by post-treatment;
[0011] S2: Under nitrogen protection, 1,4-cyclohexane diisocyanate, diethyl N,N-bis(2-hydroxyethyl)aminomethylenephosphonate, and diethylene glycol adipate react under the action of a catalyst, dibutyltin dilaurate, to obtain a polyurethane prepolymer;
[0012] S3: Under nitrogen protection, polyurethane prepolymer, 2,2-dihydroxymethylpropionic acid and 1,4-butanediol undergo chain extension reaction under the action of dibutyltin dilaurate as a catalyst to obtain polyurethane emulsion;
[0013] S4: subjecting the modified silane and the polyurethane emulsion to a post-chain extension reaction, adding triethylamine for neutralization, and then adding deionized water for emulsification to obtain an adhesive;
[0014] In step S1, the molar ratio of the methylsiloxane-terminated aminoethylaminoisobutylmethylsiloxane, the first added drop of siloxane acetyl chloride, the first added drop of triethylamine, the second added drop of siloxane acetyl chloride, and the second added drop of triethylamine is 1:(0.5-0.55):(0.5-0.6):(0.5-0.55):(0.5-0.6).
[0015] In step S2, the mass ratio of 1,4-cyclohexane diisocyanate, diethyl N,N-bis(2-hydroxyethyl)aminomethylenephosphonate and diethylene glycol adipate is (2-5):(6-8):(5-10);
[0016] In step S3, the mass ratio of the polyurethane prepolymer, 2,2-dimethylolpropionic acid, and 1,4-butanediol is (1-3):(10-15):(5-10);
[0017] In step S4, the mass ratio of the modified silane and the polyurethane emulsion is (2-6):(3-5).
[0018] The low infrared emissivity powder is modified graphene.
[0019] The modified graphene was prepared by the following method:
[0020] S1: In an ice bath, add concentrated sulfuric acid to the reactor, add phosphoric acid while stirring, then slowly add graphene and potassium permanganate, stir at 50°C for 10 hours, cool, add hydrogen peroxide, filter, centrifuge, wash, and vacuum dry to obtain graphene oxide;
[0021] S2: Add dopamine hydrochloride aqueous solution and graphene oxide aqueous solution into the reactor, ultrasonically disperse for 10 minutes, then add phosphate buffer to the mixture, stir at room temperature for 24 hours, then slowly add 3-mercaptopropionic acid, continue stirring at room temperature for 12 hours, post-treat to obtain black powder, and then place it in a tubular furnace for calcination to obtain modified graphene.
[0022] The heat insulation layer is a silica gel heat insulation layer.
[0023] The microcapsule phase change material is prepared by compounding n-tetradecane, n-octadecane and liquid paraffin in a weight ratio of 1:1:1.
[0024] The low infrared emissivity visible light pigment is one of green iron oxide, green chromium oxide and green nickel oxide.
[0025] The cross-linking agent is one of glutaraldehyde and glyoxal.
[0026] A method for preparing an infrared-proof stealth fabric comprises the following steps:
[0027] (1) soaking the fabric in an alkali solution and heating it in the alkali solution at 75° C. for 30 minutes; taking out the fabric, rinsing the fabric with deionized water until it becomes neutral, and then drying it in an oven, and then plasma treating it to obtain a fabric layer;
[0028] (2) Weighing by weight: 9-15 parts of microcapsule phase change material, 8-10 parts of low infrared emissivity powder, 2-3 parts of low infrared emissivity visible light pigment, 6-10 parts of adhesive, 3-5 parts of cross-linking agent, 4-6 parts of thickener, and 100 parts of deionized water; stirring and mixing evenly, and letting stand to obtain an infrared stealth coating;
[0029] (3) applying the infrared stealth coating to one side of the fabric layer by a scraper of a coating machine, and drying it in an oven to obtain an infrared camouflage surface layer;
[0030] (4) The heat insulation layer is laminated to the infrared camouflage surface layer and dried in an oven to obtain an infrared-proof stealth fabric.
[0031] Due to the adoption of the above technical solution, the beneficial effects of the present invention include:
[0032] (1) The present invention first prepares a modified silane by reacting the primary amine in aminoethylaminoisobutylmethylsiloxane terminated with dimethylsiloxane with the acyl chloride group in siloxane acetyl chloride; then the isocyanate group in 1,4-cyclohexane diisocyanate reacts with the hydroxyl groups in N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester and poly(diglycol adipate) to prepare a polyurethane prepolymer, and then a chain extension reaction is carried out through 2,2-dihydroxymethylpropionic acid and 1,4-butanediol; finally, the secondary amine in the modified silane reacts with the isocyanate group to carry out post-chain extension to prepare an adhesive with low infrared emissivity.
[0033] (2) The present invention prepares graphene oxide by modifying graphene, and then doping dopamine hydrochloride and 3-mercaptopropionic acid to prepare modified graphene with low infrared emissivity.
[0034] (3) The adhesive prepared by the present invention contains a carbamate group (-NH-COO-), which is the basic structural unit of polyurethane and has a strong polarity. It can absorb infrared light of a specific wavelength in the infrared spectrum, thereby reducing the infrared emissivity of the material; at the same time, the prepared adhesive contains a Si-O-Si bond, which has a strong polarity. At the same time, Si-O-Si can form intramolecular and intermolecular hydrogen bonds with the alkyl group. This hydrogen bonding can change the vibration mode of the molecule and interfere with the signal reception of the infrared detection equipment, thereby reducing the infrared emissivity.
[0035] (4) In the modified graphene prepared by the present invention, the hydroxyl and carboxyl groups rich in dopamine molecules and graphene surfaces react with the thiol groups of 3-mercaptopropionic acid. As the reaction time increases, the N and S elements enter the internal structure of the graphene, and the nitrogen element replaces the carbon element to enter the graphene structure to become graphite nitrogen; the sulfur element exists in the graphene oxide in the form of thiophene sulfur, and a thicker modified graphene with a sheet structure is obtained; and the simultaneous doping of nitrogen and sulfur changes the Fermi level of graphene, inhibits the interband transition of electrons, and thus reduces the infrared emissivity. In addition, doping with nitrogen and sulfur can also increase the specific surface area of graphene, promote the scattering and absorption of infrared radiation, and further reduce the emissivity. DETAILED DESCRIPTION
[0036] The invention will be further described below in conjunction with the embodiments, but the invention is not limited to these embodiments.
[0037] Example 1 Preparation of adhesive:
[0038] S1: Under nitrogen protection, 200g of dichloromethane and 41g of aminoethylaminoisobutylmethylsiloxane terminated with dimethylsiloxane were added to the reactor, stirred, and 11.8g of siloxane acetyl chloride and 5g of triethylamine were slowly added dropwise at 0°C for 5min. After reacting for 15min, 11.8g of siloxane acetyl chloride and 5g of triethylamine were slowly added dropwise again for 5min. After the addition, the reaction was completed for 0.5h, filtered, washed with 50ml of tetrachloroethylene and 10ml of ethanol in turn, and dried under vacuum at 50°C for 2h to obtain modified silane;
[0039] S2: Under nitrogen protection, add 200g DMSO, 20g 1,4-cyclohexane diisocyanate, and 60g N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester to the reactor, stir to dissolve, heat to 80°C, then slowly drop 50g poly(diethylene glycol adipate) (PDEGA3000) for 20min, add 0.2g catalyst dibutyltin dilaurate after the dropwise addition, react for 3h to obtain a polyurethane prepolymer;
[0040] S3: Under nitrogen protection, add 10 g of polyurethane prepolymer and 100 g of 2,2-dimethylol propionic acid to the reactor, stir and dissolve, heat to 80° C., slowly add 50 g of 1,4-butanediol and 0.5 g of dibutyltin dilaurate, react for 4 h, and obtain a polyurethane emulsion;
[0041] S4: Add 200g DMSO, 20g modified silane and 30g polyurethane emulsion into the reactor, stir to dissolve, heat to 80°C, slowly add 0.5g dibutyltin dilaurate, react for 1.5h, after the reaction, remove the solvent by evaporation, add 100g acetone to adjust the viscosity, pour into an emulsification barrel, slowly add 40g triethylamine under high-speed stirring (3000r / min) to neutralize for 10min, then add 200g deionized water and shear emulsify for 20min to obtain the adhesive.
[0042] Example 2 Preparation of adhesive:
[0043] S1: Under nitrogen protection, 200g of dichloromethane and 41g of aminoethylaminoisobutylmethylsiloxane terminated with dimethylsiloxane were added to the reactor, stirred, and 12.5g of siloxane acetyl chloride and 5.5g of triethylamine were slowly added dropwise at 0°C for 5min. After reacting for 20min, 12.5g of siloxane acetyl chloride and 5.5g of triethylamine were slowly added dropwise for 5min. After the addition was completed, the reaction lasted for 45min, filtered, washed with 50ml of tetrachloroethylene and 10ml of ethanol in turn, and dried under vacuum at 50°C for 2h to obtain modified silane;
[0044] S2: Under nitrogen protection, add 200g DMSO, 30g 1,4-cyclohexane diisocyanate, and 70g N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester to the reactor, stir to dissolve, heat to 85°C, then slowly drop 80g poly(diethylene glycol adipate) (PDEGA3000) for 20min, add 0.4g catalyst dibutyltin dilaurate after the dropwise addition, react for 4h to obtain a polyurethane prepolymer;
[0045] S3: Under nitrogen protection, add 20 g of polyurethane prepolymer and 120 g of 2,2-dimethylol propionic acid to the reactor, stir and dissolve, heat to 90° C., slowly add 80 g of 1,4-butanediol and 0.8 g of dibutyltin dilaurate, react for 5 h, and obtain a polyurethane emulsion;
[0046] S4: Add 200g DMSO, 40g modified silane and 40g polyurethane emulsion into the reactor, stir to dissolve, heat to 85°C, slowly add 0.8g dibutyltin dilaurate, react for 2h. After the reaction, remove the solvent by evaporation, add 100g acetone to adjust the viscosity, pour into an emulsification barrel, slowly add 40g triethylamine under high-speed stirring (3000r / min) to neutralize for 10min, and then add 200g deionized water to shear emulsify for 20min to obtain the adhesive.
[0047] Example 3 Preparation of adhesive:
[0048] S1: Under nitrogen protection, 200g of dichloromethane and 41g of aminoethylaminoisobutylmethylsiloxane terminated with dimethylsiloxane were added to the reactor, stirred, and 13g of siloxane acetyl chloride and 6g of triethylamine were slowly added dropwise at 0°C for 5min. After reacting for 30min, 13g of siloxane acetyl chloride and 6g of triethylamine were slowly added dropwise for 5min. After the reaction was completed for 1h, the mixture was filtered, washed with 50ml of tetrachloroethylene and 10ml of ethanol in turn, and dried under vacuum at 50°C for 2h to obtain modified silane;
[0049] S2: Under nitrogen protection, add 200g DMSO, 50g 1,4-cyclohexane diisocyanate, and 80g N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester to the reactor, stir to dissolve, heat to 90°C, then slowly drop 100g poly(diethylene glycol adipate) (PDEGA3000) for 20min, add 0.5g catalyst dibutyltin dilaurate after the dropwise addition, react for 3.5h to obtain a polyurethane prepolymer;
[0050] S3: Under nitrogen protection, 30 g of polyurethane prepolymer and 150 g of 2,2-dimethylolpropionic acid were added to the reactor and stirred to dissolve, the temperature was raised to 85° C., 100 g of 1,4-butanediol and 1.0 g of dibutyltin dilaurate were slowly added, and the reaction was carried out for 6 h to obtain a polyurethane emulsion;
[0051] S4: Add 200g DMSO, 60g modified silane and 50g polyurethane emulsion into the reactor, stir to dissolve, heat to 90°C, slowly add 1.0g dibutyltin dilaurate, react for 3h, after the reaction, remove the solvent by evaporation, add 100g acetone to adjust the viscosity, pour into an emulsification barrel, slowly add 40g triethylamine under high-speed stirring (3000r / min) to neutralize for 10min, then add 200g deionized water and shear emulsify for 20min to obtain the adhesive.
[0052] Example 4 Preparation of modified graphene:
[0053] S1: In an ice bath, 90 g of 98.3 wt% concentrated sulfuric acid was added to the reactor, and 10 g of 85 wt% phosphoric acid was added while stirring. Then, 80 g of graphene and 8 g of potassium permanganate were slowly added, and the mixture was stirred at 50 °C for 10 h. After cooling, 20 ml of 3 wt% hydrogen peroxide was added, and the mixture was stirred for 30 min. The mixture was filtered through polyester fiber, and centrifuged at 4000 r / min for 4 h. The mixture was washed with 10 mL of deionized water, 10 mL of 30 wt% HCl, and 10 mL of anhydrous ethanol in sequence. Finally, the graphene oxide was dried under vacuum at room temperature for 24 h to obtain 15 mg·mL of graphene oxide. -1 Graphene oxide aqueous solution;
[0054] S2: Add 30 ml of 12 mg mL into the reactor-1 Dopamine hydrochloride aqueous solution, 35ml15mg·mL -1 The graphene oxide aqueous solution was ultrasonically dispersed for 10 min, and then 25 ml of phosphate buffer (pH = 8.5) was added to the mixture, stirred at room temperature for 24 h, and then 0.2 g of 3-mercaptopropionic acid was slowly added, and stirring was continued at room temperature for 12 h, washed with 10 ml of deionized water and 10 ml of anhydrous ethanol, and dried in a vacuum drying oven at 60 ° C for 24 h; the obtained solid was placed in a tubular furnace and heated at 50 cm 3 / min nitrogen was introduced for 30min, the temperature was first increased to 400°C at a heating rate of 2°C / min and maintained for 2h, then the temperature was further increased to 500°C at a heating rate of 5°C / min, and then naturally decreased to room temperature to obtain modified graphene.
[0055] Example 5 Preparation of stealth fabric:
[0056] (1) The fabric is immersed in an alkaline solution composed of 6 g / L Na2CO3 and 15 g / L NaOH by mass fraction, and heated in the alkaline solution at 75°C for 30 min; the fabric is taken out, rinsed with deionized water to neutralize the fabric, and then dried in an oven at 65°C for 2 h, and then plasma treated to obtain a fabric layer;
[0057] (2) Weigh: 90 g of microcapsule phase change material (30 g of n-tetradecane, 30 g of n-octadecane, 30 g of liquid paraffin), 80 g of low infrared emissivity powder (prepared in Example 4), 20 g of low infrared emissivity visible light pigment (iron oxide green), 60 g of adhesive (prepared in Example 1), 30 g of cross-linking agent (glutaraldehyde), 40 g of thickener (DM-5230), and 1000 g of deionized water; stir and mix well to obtain an infrared stealth coating;
[0058] (3) The infrared stealth coating is scraped onto one side of the fabric layer by a scraper of a coating machine, firstly scraped by a floating knife method, wherein the floating knife amount (the height of the scraper from the base platform) is 0.2 mm, and then dried at a drying temperature of 100°C for 200 seconds; then scraped by a suspended knife method, wherein the lower knife amount (the distance of the scraper below the base plane) is 0.5 mm, the knife distance (the distance from the scraper to the base) is 3.5 mm, and then dried at a drying temperature of 90°C for 180 seconds to obtain an infrared camouflage surface layer;
[0059] (4) Laminating the heat insulation layer and the infrared camouflage surface layer, drying them in an oven at a temperature of 100° C., and cooling them to below 50° C. to obtain the infrared-proof stealth fabric.
[0060] Example 6 Preparation of Stealth Fabric:
[0061] (1) The fabric is immersed in an alkaline solution composed of 6 g / L Na2CO3 and 15 g / L NaOH by mass fraction, and heated in the alkaline solution at 75°C for 30 min; the fabric is taken out, rinsed with deionized water to neutralize the fabric, and then dried in an oven at 65°C for 2 h, and then plasma treated to obtain a fabric layer;
[0062] (2) Weigh: 120 g of microcapsule phase change material (40 g of n-tetradecane, 40 g of n-octadecane, 40 g of liquid paraffin), 90 g of low infrared emissivity powder (prepared in Example 4), 25 g of low infrared emissivity visible light pigment (chromium oxide green), 80 g of adhesive (prepared in Example 2), 40 g of cross-linking agent (glutaraldehyde), 50 g of thickener (DM-5230), and 1000 g of deionized water; stir and mix well to obtain an infrared stealth coating;
[0063] (3) The infrared stealth coating is scraped onto one side of the fabric layer by a scraper of a coating machine, firstly scraped by a floating knife method, wherein the floating knife amount (the height of the scraper from the base platform) is 0.2 mm, and then dried at a drying temperature of 100°C for 200 seconds; then scraped by a suspended knife method, wherein the lower knife amount (the distance of the scraper below the base plane) is 0.5 mm, the knife distance (the distance from the scraper to the base) is 3.5 mm, and then dried at a drying temperature of 90°C for 180 seconds to obtain an infrared camouflage surface layer;
[0064] (4) Laminating the heat insulation layer and the infrared camouflage surface layer, drying them in an oven at a temperature of 100° C., and cooling them to below 50° C. to obtain the infrared-proof stealth fabric.
[0065] Example 7 Preparation of Stealth Fabric:
[0066] (1) The fabric is immersed in an alkaline solution composed of 6 g / L Na2CO3 and 15 g / L NaOH by mass fraction, and heated in the alkaline solution at 75°C for 30 min; the fabric is taken out, rinsed with deionized water to neutralize the fabric, and then dried in an oven at 65°C for 2 h, and then plasma treated to obtain a fabric layer;
[0067] (2) Weigh: 150 g of microcapsule phase change material (50 g of n-tetradecane, 50 g of n-octadecane, 50 g of liquid paraffin), 100 g of low infrared emissivity powder (prepared in Example 4), 30 g of low infrared emissivity visible light pigment (green nickel oxide), 100 g of adhesive (prepared in Example 3), 50 g of cross-linking agent (glyoxal), 60 g of thickener (ZJ-ZCD), and 1000 g of deionized water; stir and mix well to obtain an infrared stealth coating;
[0068] (3) The infrared stealth coating is scraped onto one side of the fabric layer by a scraper of a coating machine, firstly scraped by a floating knife method, wherein the floating knife amount (the height of the scraper from the base platform) is 0.2 mm, and then dried at a drying temperature of 100°C for 200 seconds; then scraped by a suspended knife method, wherein the lower knife amount (the distance of the scraper below the base plane) is 0.5 mm, the knife distance (the distance from the scraper to the base) is 3.5 mm, and then dried at a drying temperature of 90°C for 180 seconds to obtain an infrared camouflage surface layer;
[0069] (4) Laminating the heat insulation layer and the infrared camouflage surface layer, drying them in an oven at a temperature of 100° C., and cooling them to below 50° C. to obtain the infrared-proof stealth fabric.
[0070] Comparative Example 1
[0071] An infrared-proof stealth fabric, the raw material composition and process are basically the same as those of Example 6, except that the adhesive in step (2) is replaced by an equal weight of Loctite HHD 3544F polyurethane adhesive.
[0072] Comparative Example 2
[0073] An infrared-proof stealth fabric, the raw material composition and process are basically the same as those of Example 6, the difference being that the adhesive in step (2) is replaced by an equal weight of KY3813 polyurethane adhesive.
[0074] Comparative Example 3
[0075] An infrared-proof stealth fabric, the raw material composition and process are basically the same as those of Example 6, except that the adhesive in step (2) is replaced by an adhesive prepared by the following method with an equal weight:
[0076] S1: Under nitrogen protection, add 200g DMSO, 30g 1,4-cyclohexane diisocyanate, and 70g N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester to the reactor, stir to dissolve, heat to 85°C, then slowly drop 80g poly(diethylene glycol adipate) (PDEGA3000) for 20min, add 0.4g catalyst dibutyltin dilaurate after the dropwise addition, react for 4h to obtain a polyurethane prepolymer;
[0077] S2: Under nitrogen protection, add 20g of polyurethane prepolymer and 120g of 2,2-dimethylolpropionic acid to the reactor, stir and dissolve, heat to 90°C, slowly add 80g of 1,4-butanediol and 0.8g of dibutyltin dilaurate, react for 5h, and obtain a polyurethane emulsion;
[0078] S3: Add 200g DMSO, 40g γ-aminopropyltriethoxysilane and 40g polyurethane emulsion into the reactor, stir to dissolve, heat to 85°C, slowly add 0.8g dibutyltin dilaurate, react for 2h. After the reaction, remove the solvent by evaporation, add 100g acetone to adjust the viscosity, pour into an emulsification barrel, slowly add 40g triethylamine under high-speed stirring (3000r / min) to neutralize for 10min, and then add 200g deionized water to shear emulsify for 20min to obtain the adhesive.
[0079] Comparative Example 4
[0080] An infrared-proof stealth fabric, the raw material composition and process are basically the same as those of Example 6, except that the adhesive in step (2) is replaced by an adhesive prepared by the following method with an equal weight:
[0081] S1: Under nitrogen protection, add 200g DMSO, 30g 1,4-cyclohexane diisocyanate, and 70g N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester to the reactor, stir to dissolve, heat to 85°C, then slowly drop 80g poly(diethylene glycol adipate) (PDEGA3000) for 20min, add 0.4g catalyst dibutyltin dilaurate after the dropwise addition, react for 4h to obtain a polyurethane prepolymer;
[0082] S2: Under nitrogen protection, add 20g of polyurethane prepolymer and 120g of 2,2-dimethylolpropionic acid to the reactor, stir and dissolve, heat to 90°C, slowly add 80g of 1,4-butanediol and 0.8g of dibutyltin dilaurate, react for 5h, and obtain a polyurethane emulsion;
[0083] S3: Add 200g DMSO, 40g 3-aminopropyltriethoxysilane and 40g polyurethane emulsion into the reactor, stir to dissolve, heat to 85°C, slowly add 0.8g dibutyltin dilaurate, react for 2h. After the reaction, remove the solvent by evaporation, add 100g acetone to adjust the viscosity, pour into an emulsification barrel, slowly add 40g triethylamine under high-speed stirring (3000r / min) to neutralize for 10min, and then add 200g deionized water to shear emulsify for 20min to obtain an adhesive.
[0084] Comparative Example 5
[0085] An infrared-proof stealth fabric, the raw material composition and process are basically the same as those of Example 6, except that the adhesive in step (2) is replaced by an adhesive prepared by the following method with an equal weight:
[0086] S1: Under nitrogen protection, add 200g DMSO, 30g 1,4-cyclohexane diisocyanate, and 70g N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester to the reactor, stir to dissolve, heat to 85°C, then slowly drop 80g poly(diethylene glycol adipate) (PDEGA3000) for 20min, add 0.4g catalyst dibutyltin dilaurate after the dropwise addition, react for 4h to obtain a polyurethane prepolymer;
[0087] S2: Under nitrogen protection, add 20g of polyurethane prepolymer and 120g of 2,2-dimethylolpropionic acid to the reactor, stir and dissolve, heat to 90°C, slowly add 80g of 1,4-butanediol and 0.8g of dibutyltin dilaurate, react for 5h, and obtain a polyurethane emulsion;
[0088] S3: Add 200g DMSO, 40g dimethylsiloxane-terminated aminoethylaminoisobutylmethylsiloxane, and 40g polyurethane emulsion into the reactor, stir to dissolve, heat to 85°C, slowly add 0.8g dibutyltin dilaurate, react for 2h, after the reaction, remove the solvent by evaporation, add 100g acetone to adjust the viscosity, pour into an emulsification barrel, slowly add 40g triethylamine under high-speed stirring (3000r / min) to neutralize for 10min, and then add 200g deionized water to shear emulsify for 20min to obtain an adhesive.
[0089] Comparative Example 6
[0090] An infrared-proof stealth fabric, the raw material composition and process are basically the same as those of Example 6, except that the adhesive in step (2) is replaced by an adhesive prepared by the following method with an equal weight:
[0091] S1: Under nitrogen protection, add 200g of dichloromethane and 41g of aminoethylaminoisobutylmethylsiloxane terminated with dimethylsiloxane into the reactor, stir, and slowly add 25g of siloxane acetyl chloride and 11g of triethylamine at 0°C at the same time, add for 5min, react for 60min after the addition, filter, wash with 50ml of tetrachloroethylene and 10ml of ethanol, and dry under vacuum at 50°C for 2h to obtain modified silane;
[0092] S2: Under nitrogen protection, add 200g DMSO, 30g 1,4-cyclohexane diisocyanate, and 70g N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester to the reactor, stir to dissolve, heat to 85°C, then slowly drop 80g poly(diethylene glycol adipate) (PDEGA3000) for 20min, add 0.4g catalyst dibutyltin dilaurate after the dropwise addition, react for 4h to obtain a polyurethane prepolymer;
[0093] S3: Under nitrogen protection, add 20 g of polyurethane prepolymer and 120 g of 2,2-dimethylol propionic acid to the reactor, stir and dissolve, heat to 90° C., slowly add 80 g of 1,4-butanediol and 0.8 g of dibutyltin dilaurate, react for 5 h, and obtain a polyurethane emulsion;
[0094] S4: Add 200g DMSO, 40g modified silane and 40g polyurethane emulsion into the reactor, stir to dissolve, heat to 85°C, slowly add 0.8g dibutyltin dilaurate, react for 2h. After the reaction, remove the solvent by evaporation, add 100g acetone to adjust the viscosity, pour into an emulsification barrel, slowly add 40g triethylamine under high-speed stirring (3000r / min) to neutralize for 10min, and then add 200g deionized water to shear emulsify for 20min to obtain the adhesive.
[0095] Comparative Example 7
[0096] An infrared-proof stealth fabric, the raw material composition and process are basically the same as those of Example 6, except that the adhesive in step (2) is replaced by an adhesive prepared by the following method with an equal weight:
[0097] S1: Under nitrogen protection, 200g of dichloromethane, 41g of aminoethylaminoisobutylmethylsiloxane terminated with dimethylsiloxane and 11g of triethylamine were added to the reactor, stirred, 12.5g of siloxane acetyl chloride was slowly added dropwise at 0°C for 5min, reacted for 20min, and then 12.5g of siloxane acetyl chloride was slowly added dropwise for 5min. After the addition was completed, the reaction lasted for 45min, filtered, washed with 50ml of tetrachloroethylene and 10ml of ethanol, and dried under vacuum at 50°C for 2h to obtain modified silane;
[0098] S2: Under nitrogen protection, add 200g DMSO, 30g 1,4-cyclohexane diisocyanate, and 70g N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester to the reactor, stir to dissolve, heat to 85°C, then slowly drop 80g poly(diethylene glycol adipate) (PDEGA3000) for 20min, add 0.4g catalyst dibutyltin dilaurate after the dropwise addition, react for 4h to obtain a polyurethane prepolymer;
[0099] S3: Under nitrogen protection, add 20 g of polyurethane prepolymer and 120 g of 2,2-dimethylol propionic acid to the reactor, stir and dissolve, heat to 90° C., slowly add 80 g of 1,4-butanediol and 0.8 g of dibutyltin dilaurate, react for 5 h, and obtain a polyurethane emulsion;
[0100] S4: Add 200g DMSO, 40g modified silane and 40g polyurethane emulsion into the reactor, stir to dissolve, heat to 85°C, slowly add 0.8g dibutyltin dilaurate, react for 2h. After the reaction, remove the solvent by evaporation, add 100g acetone to adjust the viscosity, pour into an emulsification barrel, slowly add 40g triethylamine under high-speed stirring (3000r / min) to neutralize for 10min, and then add 200g deionized water to shear emulsify for 20min to obtain the adhesive.
[0101] Comparative Example 8
[0102] An anti-infrared stealth fabric, the raw material composition and process are basically the same as those of Example 6, the difference being that the low infrared emissivity powder in step (2) is replaced by an equal weight of graphene.
[0103] Comparative Example 9
[0104] An anti-infrared stealth fabric, the raw material composition and process are basically the same as those of Example 6, the difference being that the low infrared emissivity powder in step (2) is replaced by an equal weight of dried graphene oxide solid prepared in step S1 of Example 4.
[0105] Comparative Example 10
[0106] An anti-infrared stealth fabric, the raw material composition and process are basically the same as those of Example 6, the difference being that the low infrared emissivity powder in step (2) is replaced by an equal weight of modified graphene prepared by the following method:
[0107] S1: In an ice bath, 90 g of 98.3 wt% concentrated sulfuric acid was added to the reactor, and 10 g of 85 wt% phosphoric acid was added while stirring. Then, 80 g of graphene and 8 g of potassium permanganate were slowly added, and the mixture was stirred at 50 °C for 10 h. After cooling, 20 ml of 3 wt% hydrogen peroxide was added, and the mixture was stirred for 30 min. The mixture was filtered through polyester fiber, and centrifuged at 4000 r / min for 4 h. The mixture was washed with 10 mL of deionized water, 10 mL of 30 wt% HCl, and 10 mL of anhydrous ethanol in sequence. Finally, the graphene oxide was dried under vacuum at room temperature for 24 h to obtain 15 mg·mL of graphene oxide. -1 Graphene oxide aqueous solution;
[0108] S2: Add 35 ml of 15 mg mL into the reactor -1 The graphene oxide aqueous solution and 0.2 g of 3-mercaptopropionic acid were ultrasonically dispersed for 10 min, stirred at room temperature for 12 h, washed with 10 ml of deionized water and 10 ml of anhydrous ethanol, and the obtained solid was dried in a vacuum oven at 60 ° C for 24 h; the obtained solid was placed in a tube furnace and heated at 50 cm 3 / min nitrogen was introduced for 30min, the temperature was first increased to 400°C at a heating rate of 2°C / min and maintained for 2h, then the temperature was further increased to 500°C at a heating rate of 5°C / min, and then naturally decreased to room temperature to obtain modified graphene.
[0109] Comparative Example 11
[0110] An anti-infrared stealth fabric, the raw material composition and process are basically the same as those of Example 6, the difference being that the low infrared emissivity powder in step (2) is replaced by an equal weight of modified graphene prepared by the following method:
[0111] S1: In an ice bath, 90 g of 98.3 wt% concentrated sulfuric acid was added to the reactor, and 10 g of 85 wt% phosphoric acid was added while stirring, and then 80 g of graphene and 8 g of potassium permanganate were slowly added, stirred at 50 °C for 10 h, cooled, and 20 ml of 3 wt% hydrogen peroxide was added, stirred for 30 min, filtered through polyester fiber, centrifuged at 4000 r / min for 4 h, washed with 10 mL of deionized water, 10 mL of 30 wt% HCl, and 10 mL of anhydrous ethanol, and finally dried under vacuum at room temperature for 24 h to obtain graphene oxide. The graphene oxide was dispersed in water to obtain 15 mg·mL -1 Graphene oxide aqueous solution;
[0112] S2: Add 30 ml of 12 mg mL into the reactor -1 Dopamine hydrochloride aqueous solution, 35ml15mg·mL -1 The graphene oxide aqueous solution was ultrasonically dispersed for 10 min, and then 25 ml of phosphate buffer (pH = 8.5) was added to the mixture, stirred at room temperature for 24 h, washed with 10 ml of deionized water and 10 ml of anhydrous ethanol, and the obtained solid was dried in a vacuum drying oven at 60 ° C for 24 h; the obtained solid was placed in a tube furnace and heated at 50 cm 3 / min nitrogen was introduced for 30min, the temperature was first increased to 400°C at a heating rate of 2°C / min and maintained for 2h, then the temperature was further increased to 500°C at a heating rate of 5°C / min, and then naturally decreased to room temperature to obtain modified graphene.
[0113] Comparative Example 12
[0114] A double-sided coated fabric is prepared using the raw material composition, proportion and method of Example 1 of the Chinese invention patent with publication number CN105316945A.
[0115] The thickness of the silica gel insulation layer used in the examples and comparative examples of the present application is 1 mm, which is purchased from Guangdong Alison Technology Co., Ltd.; the DM-5230 thickener is purchased from Guangdong Demei Fine Chemical Group Co., Ltd.; the ZJ-ZCD thickener is purchased from Guangzhou Zhuangjie Chemical Co., Ltd.; the fabric used is 500D polyester filament Oxford cloth (202 roots / 10cm×154 roots / 10cm, gram weight: 205g / m, Zhejiang Fa Textile Printing and Dyeing Co., Ltd.); the concentration of graphene used is 2mg / mL (DMF solvent), the average radial size is 5-8μm, and the thickness is 1nm; the CAS number of dimethylsiloxane-terminated aminoethylaminoisobutylmethylsiloxane is 106842-44-8; the structural formula of siloxane acetyl chloride is as follows:
[0116]
[0117] The equipment used for plasma treatment in the embodiments and comparative examples of the present application is GY-RTR type film / fabric plasma treatment equipment, and the specific process parameters are: treatment gas: air, treatment time: 80 seconds, treatment frequency: 1.3kHz, discharge distance: 2cm, and plate spacing: 2cm.
[0118] The infrared-proof stealth fabrics prepared in Examples 5-7 and Comparative Examples 1-12 of the present application were subjected to an infrared emissivity test. The test method was based on GJB 5023.2-2003 "Test methods for reflectivity and emissivity of materials and coatings Part 2: Emissivity". The test results are shown in Table 1.
[0119] Table 1
[0120]
[0121]
[0122] It can be seen from Table 1 that the infrared emissivity of the anti-infrared stealth fabric prepared by the present invention is lower than 0.33, and has excellent low infrared emissivity.
[0123] The raw material composition and process of Comparative Example 1 are basically the same as those of Example 6, except that the adhesive is replaced with an equal weight of Loctite HHD 3544F polyurethane adhesive. It can be seen from the data in Table 1 that its infrared emissivity is 0.786, which is relatively high, indicating that the stealth performance of the commercially available adhesive is not as good as the adhesive prepared in the present application.
[0124] The raw material composition and process of Comparative Example 2 are basically the same as those of Example 6, except that the adhesive is replaced with an equal weight of KY3813 polyurethane adhesive. It can be seen from the data in Table 1 that its infrared emissivity is 0.742, which is relatively high and has poor stealth performance.
[0125] The raw material composition and process of Comparative Example 3 are basically the same as those of Example 6, except that when preparing the adhesive, the modified silane in step S3 is replaced by an equal weight of γ-aminopropyltriethoxysilane. It can be seen from the data in Table 1 that its infrared emissivity is 0.643, and the infrared emissivity is relatively high. This is because γ-aminopropyltriethoxysilane contains ethoxy groups. When the amino group in the silane coupling agent reacts with the isocyanate group, the triethoxysilane is connected to both ends of the polyurethane segment. During emulsification, the ethoxy group is hydrolyzed into hydroxyl groups when it encounters water, resulting in the instability of the prepared adhesive molecules, thereby making the infrared emissivity higher.
[0126] The raw material composition and process of Comparative Example 4 are basically the same as those of Example 6. The difference is that when preparing the adhesive, the modified silane in step S3 is replaced by an equal weight of 3-aminopropyltriethoxysilane. It can be seen from the data in Table 1 that its infrared emissivity is 0.607, which has a relatively high infrared emissivity. 3-aminopropyltriethoxysilane also contains ethoxy groups, which will hydrolyze when encountering water. The principle is the same as that of Comparative Example 3.
[0127] The raw material composition and process of Comparative Example 5 are basically the same as those of Example 6, except that the modified silane in step S3 of the adhesive preparation process is replaced by an equal weight of dimethylsiloxane-terminated aminoethylaminoisobutylmethylsiloxane. It can be seen from the data in Table 1 that its infrared emissivity is 0.588, which is not as good as the infrared stealth fabric prepared in this application.
[0128] The raw material composition and process of Comparative Examples 6 and 7 are basically the same as those of Example 6, except that modified silanes prepared by different preparation methods are used in the preparation of the adhesive. It can be seen from Table 1 that their infrared emissivities are 0.497 and 0.543, respectively. The reason is that the aminoethylaminoisobutylmethylsiloxane terminated with dimethylsiloxane contains primary amines and secondary amines. Although the activity of secondary amines is not as good as that of primary amines, in theory, secondary amines should react with acyl chlorides first. However, when acyl chlorides are added to the aminoethylaminoisobutylmethylsiloxane terminated with dimethylsiloxane, both primary amines and secondary amines will react, but the reaction rate of primary amines will be higher than that of secondary amines. However, when the primary amines and secondary amines on the same molecule react with acyl chlorides to form amides, the siloxane of the molecule will not be able to modify the polyurethane emulsion because amides are difficult to react with isocyanates. In order to ensure the reaction of the primary amine, siloxane acetyl chloride and triethylamine were slowly added in batches to slow down the rate of the forward reaction, increase the competitive advantage of the primary amine reaction, and make the primary amine react with the acyl chloride first, thereby reducing the possibility of the secondary amine reacting.
[0129] The raw material composition and process of Comparative Example 8 are basically the same as those of Example 6, except that the modified graphene is replaced with graphene of equal weight. It can be seen from the data in Table 1 that its infrared emissivity is 0.536, indicating that pure graphene has a higher infrared emissivity when used as a low infrared emissivity powder.
[0130] The raw material composition and process of Comparative Example 9 are basically the same as those of Example 6, except that the modified graphene is replaced by an equal weight of graphene oxide prepared in step S1 of Example 4. It can be seen from the data in Table 1 that its infrared emissivity is 0.501, and the infrared emissivity is average, indicating that after the graphene is oxidized, the infrared emissivity is improved, but it is still not as good as the modified graphene.
[0131] The raw material composition and process of Comparative Example 10 are basically the same as those of Example 6, except that dopamine hydrochloride is not added in step S2 of the modified graphene preparation process. It can be seen from the data in Table 1 that its infrared emissivity is 0.427.
[0132] The raw material composition and process of Comparative Example 11 are basically the same as those of Example 6, except that 3-mercaptopropionic acid is not added in step S2 during the preparation of the modified graphene. It can be seen from the data in Table 1 that its infrared emissivity is 0.433. When no sulfur element is added to the modified graphene, the infrared emissivity also decreases, indicating that nitrogen and sulfur elements complement each other and work together to reduce the infrared emissivity.
[0133] Comparative Example 12 is a double-sided coated fabric prepared using the raw material composition, ratio and method of Example 1 of the Chinese invention patent with publication number CN105316945A. It can be seen from the data in Table 1 that its infrared emissivity is 0.573, which is not as good as the stealth fabric prepared in this application.
[0134] The anti-infrared stealth fabrics prepared in Examples 5-7 and Comparative Examples 1-12 of the present application were subjected to a flame retardant performance test. The test method was carried out in accordance with GB / T 5455-1997 "Vertical method for testing the burning performance of textiles". The test results are shown in Table 2.
[0135] Table 2
[0136]
[0137]
[0138] It can be seen from Table 2 that the anti-infrared stealth fabric prepared in the present application has excellent flame retardant properties. The reason is that phosphate groups are introduced in the adhesive preparation process (the phosphate groups introduced in Comparative Examples 6-7 are less), and the phosphate groups can form a carbon layer under high temperature conditions. The carbon layer can effectively isolate the interior of the material and slow down its burning rate, thereby achieving a flame retardant effect.
[0139] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. An anti-infrared stealth fabric, characterized in that: The infrared camouflage surface layer and the heat insulation layer are sequentially included from the outside to the inside, and the infrared camouflage surface layer sequentially includes the infrared stealth coating and the fabric layer from the outside to the inside; The infrared stealth coating comprises the following raw materials in parts by weight: 9-15 parts of microcapsule phase change material, 8-10 parts of low infrared emissivity powder, 2-3 parts of low infrared emissivity visible light pigment, 6-10 parts of adhesive, 3-5 parts of cross-linking agent, 4-6 parts of thickener, and 100 parts of deionized water; The adhesive is prepared by the following method: S1: Under nitrogen protection, dichloromethane and aminoethylaminoisobutylmethylsiloxane terminated with dimethylsiloxane were added to the reactor, stirred, and siloxane acetyl chloride and triethylamine were slowly added dropwise at 0°C, reacted for 15-30 minutes, and then siloxane acetyl chloride and triethylamine were slowly added dropwise. The reaction was continued for 0.5-1 hour, and the modified silane was obtained by post-treatment; S2: Under nitrogen protection, 1,4-cyclohexane diisocyanate, diethyl N,N-bis(2-hydroxyethyl)aminomethylenephosphonate, and diethylene glycol adipate react under the action of a catalyst, dibutyltin dilaurate, to obtain a polyurethane prepolymer; S3: Under nitrogen protection, polyurethane prepolymer, 2,2-dihydroxymethylpropionic acid and 1,4-butanediol undergo chain extension reaction under the action of dibutyltin dilaurate as a catalyst to obtain polyurethane emulsion; S4: subjecting the modified silane and the polyurethane emulsion to a post-chain extension reaction, adding triethylamine for neutralization, and then adding deionized water for emulsification to obtain an adhesive; In step S1, the molar ratio of the methylsiloxane-terminated aminoethylaminoisobutylmethylsiloxane, the first added drop of siloxane acetyl chloride, the first added drop of triethylamine, the second added drop of siloxane acetyl chloride, and the second added drop of triethylamine is 1:(0.5-0.55):(0.5-0.6):(0.5-0.55):(0.5-0.6).
2. The anti-infrared stealth fabric according to claim 1, characterized in that: In step S2, the mass ratio of 1,4-cyclohexane diisocyanate, diethyl N,N-bis(2-hydroxyethyl)aminomethylenephosphonate and diethylene glycol adipate is (2-5):(6-8):(5-10); In step S3, the mass ratio of the polyurethane prepolymer, 2,2-dimethylolpropionic acid, and 1,4-butanediol is (1-3):(10-15):(5-10); In step S4, the mass ratio of the modified silane and the polyurethane emulsion is (2-6):(3-5).
3. The anti-infrared stealth fabric according to claim 1, characterized in that: The low infrared emissivity powder is modified graphene.
4. The anti-infrared stealth fabric according to claim 3, characterized in that: The modified graphene is prepared by the following method: S1: In an ice bath, add concentrated sulfuric acid to the reactor, add phosphoric acid while stirring, then slowly add graphene and potassium permanganate, stir at 50°C for 10 hours, cool, add hydrogen peroxide, filter, centrifuge, wash, and vacuum dry to obtain graphene oxide, and disperse the graphene oxide in water to obtain a graphene oxide aqueous solution; S2: Add dopamine hydrochloride aqueous solution and graphene oxide aqueous solution into the reactor, ultrasonically disperse for 10 minutes, then add phosphate buffer to the mixture, stir at room temperature for 24 hours, then slowly add 3-mercaptopropionic acid, continue stirring at room temperature for 12 hours, post-treat to obtain black powder, and then place it in a tubular furnace for calcination to obtain modified graphene.
5. The anti-infrared stealth fabric according to claim 1, characterized in that: The heat insulation layer is a silica gel heat insulation layer.
6. The anti-infrared stealth fabric according to claim 1, characterized in that: The microcapsule phase change material is prepared by compounding n-tetradecane, n-octadecane and liquid paraffin in a weight ratio of 1:1:
1.
7. The anti-infrared stealth fabric according to claim 1, characterized in that: The low infrared emissivity visible light pigment is one of green iron oxide, green chromium oxide and green nickel oxide.
8. The anti-infrared stealth fabric according to claim 1, characterized in that: The cross-linking agent is one of glutaraldehyde and glyoxal.
9. A method for preparing the infrared-proof stealth fabric according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) soaking the fabric in an alkali solution and heating it in the alkali solution at 75° C. for 30 minutes; taking out the fabric, rinsing the fabric with deionized water until it becomes neutral, and then drying it in an oven, and then plasma treating it to obtain a fabric layer; (2) Weighing by weight: 9-15 parts of microcapsule phase change material, 8-10 parts of low infrared emissivity powder, 2-3 parts of low infrared emissivity visible light pigment, 6-10 parts of adhesive, 3-5 parts of cross-linking agent, 4-6 parts of thickener, and 100 parts of deionized water; stirring and mixing to obtain an infrared stealth coating; (3) applying the infrared stealth coating to one side of the fabric layer by a scraper of a coating machine, and drying it in an oven to obtain an infrared camouflage surface layer; (4) The heat insulation layer is laminated to the infrared camouflage surface layer and dried in an oven to obtain an infrared-proof stealth fabric.
Citation Information
Patent Citations
Double-side coating fabric
CN105316945A